The Influence of Problem Based Learning Model For Student Competence In Computer System Learning Eyes Reviewed From Class X Multimedia Achievement Motivation In Vocational School 10 Surabaya - Agusvianto, Hendra; Basuki, Ismet; Ismayati, Euis (International Journal for Educational and Vocational Studies, 2020)
The process of teaching and learning activities uses problems in daily life as a form of improving thinking skills and problem solving, as well as gaining important concept knowledge by using student achievement motivation on computer systems subjects on computer system attitude competencies, computer system knowledge competencies, and competency skills computer system. Teachers at SMKN 10 Surabaya on average use the STAD cooperative model and students' competencies are taught low while researchers use the Problem Based Learning model and make student competencies increase.The design of this study uses 2 x 2 factorial analysis design with independent variables Problem Based Learning models and STAD cooperative models, moderating variables of high achievers motivation and low achievers motivation, and dependent variables competency in computer system attitudes, computer knowledge of computer systems, and computer system skills competencies.The results of this study in Multimedia 10 class students who were taught using PBL learning models were very significant competency compared to STAD cooperatives